Akuntansi Dalam Era Industri 4.0: - Juliana Nasution; Asriatun Fauziah Dalimunthe (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to identify and analyze the opportunities and challenges faced by professional accountants, how accountants deal with technological advances, and technological developments in the Industrial Revolution Era 4.0. The approach used in this research is qualitative. The sample in this study consisted of 4 informants at PT. Eriadi Fatkhur Rokhman. The data collection technique in this research is to conduct structured interviewsThe results show that if accountants must be technology literate and able to adapt to technology, even though technology will not eliminate the accounting profession but will reshape it with new and challenging responsibilities, it is likely that some of the accounting profession's work will be taken over by technology, accountants will turn into interpreter, or analyze and interpret data, so that the accounting profession can continue to survive, therefore, accountants must be able to follow existing developments. Keywords: Accountant, Industrial Revolution 4.0, PT. Eriadi Fatkhur Rokhman, Technology